A comparison between ultrafine WC-Co and fine WC-VC-Co alloys. (1st January 2000) - Randt, D. du; Luyckx, S.; Marcoulides, D.; Northrop, I.T.; Whitefield, D.J.
During the last few years WC-VC-Co alloys have been developed starting from V8 C7, WC and Co powders. After sintering, the alloys are composed of WC, (W, V)C and Co and, at a mean carbide grain size of 1-2 µm, which can be defined as "fine", they exhibit a hardness which is equal or superior to that of the hardest WC-Co alloys of equal cobalt content (1). The hardest WC-Co alloys which are in production at present have mean grain size of approximately 0.4 µm and are usually referred to as "ultrafine" (2). This paper compares the hardness as well as other properties of ultrafine WC-Co and fine WC-VC-Co alloys.